Technical quality of online resources for mobility device training. (17th February 2022) - Best, Krista L.; Beaudoin, Maude; Routhier, François
Abstract: Purpose: Training is recommended to improve safe and effective use of mobility aids. The internet offers a large amount of information and it can be difficult to identify resources with good quality. This project aimed to create a catalogue of online educational resources for mobility device training. The objective of this study was to identify and assess the quality of existing online educational resources for mobility device training for individuals with physical disabilities and caregivers. Methods: A Google search was conducted in October 2016 and replicated in January 2018. Resources were included if they were educational, were available in English or French, provided instruction or training in mobility aid use, were free of charge, and were targeted towards mobility device users or their caregivers. Resources were assessed using a modified version of the Journal of the American Medical Association (JAMA) benchmarks for the evaluation of technical quality. Results: Two hundred and seventy-one resources were included in the final analysis. Two resources were added by the research team for a total of 273 resources. The average JAMA quality score per mobility device varied between 3 (for crutches) and 5 (for knee scooters) out of 6, and weighted average was 3.6. The two resources added by the research team obtained a JAMA quality score of 6. 58 resources were retained for the catalogue. Conclusions: The results suggest that the technical quality of online educational resources for mobility device training could be improved. A need for higher quality resources for device users and caregivers was identified. Implications for rehabilitation: The overall technical quality of online educational resources for mobility device training for users and caregivers is low. A Mobility Device Training Catalogue is freely available and summarizes the highest quality online resources found on mobility device training. The Mobility Device Training Catalogue is intended for use by users and caregivers, but it may also provide clinicians with a tool that may be shared with their clients.